2024
DOI: 10.1038/s41598-024-53148-3
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of sensorimotor temporal recalibration mechanisms by cerebellar tDCS in patients with schizophrenia spectrum disorders and healthy individuals

Christina V. Schmitter,
Benjamin Straube

Abstract: Core symptoms in patients with schizophrenia spectrum disorders (SSD), like hallucinations or ego-disturbances, have been associated with a failure of internal forward models to predict the sensory outcomes of self-generated actions. Importantly, forward model predictions must also be able to flexibly recalibrate to changing environmental conditions, for example to account for additional delays between action and outcome. We investigated whether transcranial direct current stimulation (tDCS) can be used to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…If future studies can uncover a neurobiological basis for the parameters governing variational BCI, their manipulation using TMS could be of high scientific and therapeutic interest. Using transcranial direct current stimulation (tDCS) improvements in delay detection (Straube et al, 2020) and delay adaptation (Schmitter & Straube, 2024) had been already shown in patients with schizophrenia spectrum disorders. However, the BCI could improve our understanding of which parameter exactly contributed to these initial findings.…”
Section: Figure 6 Example Of Simulated Trials With Optimized Paramete...mentioning
confidence: 99%
“…If future studies can uncover a neurobiological basis for the parameters governing variational BCI, their manipulation using TMS could be of high scientific and therapeutic interest. Using transcranial direct current stimulation (tDCS) improvements in delay detection (Straube et al, 2020) and delay adaptation (Schmitter & Straube, 2024) had been already shown in patients with schizophrenia spectrum disorders. However, the BCI could improve our understanding of which parameter exactly contributed to these initial findings.…”
Section: Figure 6 Example Of Simulated Trials With Optimized Paramete...mentioning
confidence: 99%